Web Science in Medicine and Healthcare - Denecke, K.; Brooks, E. (Methods of Information in Medicine, 2013)
Objectives: Medical social-media provide a new source of information within information gaining contexts. Facts, experiences, opinions or information on behaviour can be found in the medical web and could support a broad range of applications. The intention of this Focus Theme is to bring the existing research together and to show the possi -bilities, challenges and technologies for Web Science in medicine and healthcare.Methods: This editorial provides an overview on the landscape of medical social-media and their possibilities in supporting healthcare. Further, it summarizes the three papers included in this Focus Theme.Results and Conclusions: The three papers of this Focus Theme consider different aspects of Web Science in medicine which are 1) detection of drug interactions from social media, 2) inferring community structures from online forums and 3) improving access to online videos through assignment of SNOMED CT terms. All three papers show the potential of medical social-media in support -ing health information gathering processes from the web. However, several issues still need to be addressed in future: Methods are necessary for identifying high quality information from the medical web as well as for processing the language that is used by social media users to report about their symptoms, diseases and other health issues.
Keywords: Web science; Social media; Medicine 2.0; Health 2.0; Information extraction